Investigation of Factors That Former CRM Quality and Its Implications for Customer Loyalty (Studies on JakOne Mobile Banking Users) - Rema Injani Milenia; Santi Rimadias (STIE Indonesia Banking School, 2022)
This study aims to identify the factors forming CRM Quality and their implications for Customer Loyalty at JakOne mobile banking users who are customers of Bank DKI Jakarta Barat Mayor Service Office. The sample used in this study were 144 JakOne mobile banking users who are customers of Bank DKI Jakarta Barat Mayor Service Office. The data collection technique in this study uses primary data by distributing questionnaires to respondents using Structural Equation Modeling (SEM) analysis which is supported by SmartPLS 3.0 applications. The main research results show that CRM Quality has a positive influence on Customer Loyalty and Customer Satisfaction has a positive influence on Customer Loyalty through CRM Quality mediation. Meanwhile, Customer Value has no influence on Customer Loyalty through CRM Quality mediation. Brand Image has no influence on Customer Loyalty, and Service Quality does not have a positive influence on Customer Loyalty through CRM Quality mediation.